(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the historical and chronological development of artificial intelligence representations in science fiction literature. The primary objective is to explore how AI characters have been aesthetically constructed and how their evolution reflects shifting philosophical, ethical, and sociocultural paradigms. Through the analysis of these fictional portrayals, the study seeks to uncover how societies have imagined technology over time — revealing both the anxieties and aspirations that accompany technological advancement